2000
DOI: 10.1002/(sici)1521-3773(20000117)39:2<398::aid-anie398>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Aliphatic Hydroxylation by a Bis(μ-oxo)dicopper(III) Complex

Abstract: By using molecular oxygen bis(µ-oxo)dicopper(III) complexes can be produced from Cu(I) complexes with ligand L(X) (L(X)=p-substituted N-ethyl-N-[2-(2-pyridyl)ethyl]-2-phenylethylamine; X=OMe, Me, H, Cl, NO(2)) in which the benzylic position of the ligand is activated and hydroxylated by the Cu(2)O(2) core (see reaction scheme). Detailed characterization of this new C-H bond activation reaction by the bis(µ-oxo)dicopper(III) core reveals important information on the fundamental chemistry underlying copper monoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 6 publications
8
115
0
Order By: Relevance
“…Namely, copper(I) complex of a tetradentate ligand such as TPA [tris(2-pyridylmethyl)amine] affords the end-on peroxo dicopper(II) complex (A) in the reaction with O 2 at a low temperature [6,29], 1;2 whereas the same reaction with a tridentate ligand such as N -alkyl-bis[2-(2-pyridyl)ethyl] amine derivative (Py2 R ) predominantly provides the side-on peroxo dicopper(II) complex (B) [5,8,30,31]. 3 Furthermore, we have recently demonstrated that oxygenation of copper(I) complexes supported by didentate ligands, N ; N -dialkyl-2-(2-pyridyl)ethylamine (Py1 R;R 0 ), affords not only the (l-g 2 :g 2 -peroxo)dicopper(II) complex (B) but also the bis(l-oxo)dicopper(III) complex (C) under the same experimental conditions [32,33]. These results stimulated us to investigate the dioxygenreactivity of dicopper(I) complexes unsymmetrically coordinated by a set of tetradentate (N 4 )/tridentate (N 3 ) and tridentate (N 3 )/didentate (N 2 ) metal binding units.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Namely, copper(I) complex of a tetradentate ligand such as TPA [tris(2-pyridylmethyl)amine] affords the end-on peroxo dicopper(II) complex (A) in the reaction with O 2 at a low temperature [6,29], 1;2 whereas the same reaction with a tridentate ligand such as N -alkyl-bis[2-(2-pyridyl)ethyl] amine derivative (Py2 R ) predominantly provides the side-on peroxo dicopper(II) complex (B) [5,8,30,31]. 3 Furthermore, we have recently demonstrated that oxygenation of copper(I) complexes supported by didentate ligands, N ; N -dialkyl-2-(2-pyridyl)ethylamine (Py1 R;R 0 ), affords not only the (l-g 2 :g 2 -peroxo)dicopper(II) complex (B) but also the bis(l-oxo)dicopper(III) complex (C) under the same experimental conditions [32,33]. These results stimulated us to investigate the dioxygenreactivity of dicopper(I) complexes unsymmetrically coordinated by a set of tetradentate (N 4 )/tridentate (N 3 ) and tridentate (N 3 )/didentate (N 2 ) metal binding units.…”
Section: Introductionsupporting
confidence: 64%
“…4, where a strong absorption band at 350 nm together with a shoulder around 400 nm and a very broad absorption band at 510 nm are observed. The absorption bands at 350 and 510 nm are very close to those of the (l-g 2 :g 2 - peroxo)dicopper(II) complex (B) [7,8,30] and the band at $400 nm is reminiscent of the bis(l-oxo)dicopper(III) complex (C) [11,12,32]. Resonance Raman spectra of the oxygenated solutions are shown in Fig.…”
Section: Dioxygen Reactivity Of Dicopper(i) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…17 The construction of highvalent M 2 (-O) 2 components is important as one of the motifs to construct a homogeneous catalyst, which activates oxygen molecule to oxidize the substrates. [18][19][20][21][22][23][24] In metalloproteins, hydrogen-bonding interaction sometimes occurs between an external molecule and the active site. For example, in myoglobin (Mb), which stores oxygen molecules in muscles, the distal histidine imidazole interacts to the dioxygen molecule bound to heme iron via hydrogen bonding.…”
Section: -Oh)-(-omentioning
confidence: 99%
“…The oxidative hydroxylation of aliphatic and aro matic fragments of the ligands in the presence of copper(II) ions was documented. 38, 39 It is suggested that the hydr oxylation occurs through the formation of the Cu II oxo dimer followed by the intramolecular nucleophilic attack of the oxygen atom of the bridging fragment on the carbon atom of the aliphatic or aromatic moieties of the mole cule. In our case, the formation of compounds 8 and 9 is most likely attributed to the conditions of the synthesis (electrochemical oxidation) and the presence of copper(II) ions in the reaction mixture.…”
Section: R = H Nomentioning
confidence: 68%